Global avian influenza situation (2019–2022). Host range expansion asevidence of high pathogenicity avian influenza virus evolution - M. V. Zhiltsova; T. P. Akimova; A. V. Varkentin; M. N. Mitrofanova; A. V. Mazneva; V. P. Semakina; E. S. Vystavkina (Ветеринария сегодня)
High pathogenicity avian inﬂuenza has a signiﬁcant negative impact on poultry farming, international trade and health of wild bird populations, therefore the infection requires the utmost attention of the entire international community. The article investigates the evolutionary and epidemic processes observed in recent years in many countries of the world where avian inﬂuenza outbreaks occur; describes the ways of the infection spread; the prevalence of the virus types for the last several years, as well as the expansion of the host range, including among representatives of the Mammalia class. The change in the ratio between the virus types starting from 2020, when H5N8 subtype was responsible for the overwhelming number of the disease outbreaks reported, until 2022, when an obvious predominance of H5N1 subtype was detected is demonstrated. A noticeable expansion of the disease-aﬀected areas in Central and South America, the inﬂuence of migration, anthropogenic and other factors on inﬂuenza spread are highlighted. The conditions facilitating the occurrence of the infection outbreaks aﬀecting mammals, wild animals and livestock, zoo and companion animals are described. Cases of mammals’ infection on the North American and Eurasian continents in zoos, nature parks, backyards and fur farms, asa rule, coincide in time with the infection outbreaks in waterfowl populations. The WAHIS data were analyzed and the high ability of the virus to spillover from birds to mammals, such as martens (minks, otters, ferrets, badgers), cats (domestic cats, cougars, leopards, lynxes), pinnipeds (common seals, grey seals), bears (brown, grizzly, American black), bottlenose dolphins, skunks, foxes, opossums, raccoons was demonstrated. Changes in the habitats of both migratory birds and mammals, including due to some human economic activities, add an ecological and urban component to the complex task of the control and prevention of the epidemic, also posing a potential threat to humans.